The Influence of Price, Facilities, and Service Quality on Parental Satisfaction (At Nurul Huda Elementary School in Surabaya City) - NURLAILIYAH, Shinta (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to further examine the